Alemtuzumab treatment of multiple sclerosis: long-term safety and efficacy. Issue 2 (21st May 2014) - Tuohy, Orla; Costelloe, Lisa; Hill-Cawthorne, Grant; Bjornson, Ingunn; Harding, Katharine; Robertson, Neil; May, Karen; Button, Tom; Azzopardi, Laura; Kousin-Ezewu, Onajite; Fahey, Michael T; Jones, Joanne; et al.
Abstract : Objectives: Alemtuzumab is a newly licensed treatment of active relapsing-remitting multiple sclerosis (RRMS) in Europe, which in phase II and III studies demonstrated superior efficacy over β-interferon in reducing disability progression over 2–3 years. In this observational cohort study, we sought to describe our longer-term experience of the efficacy and safety of alemtuzumab in active RRMS. Methods: Clinical and laboratory data including serial Expanded Disability Status Scale (EDSS) assessments, from all 87 patients treated with alemtuzumab on investigator-led studies in Cambridge, UK, from 1999 to 2012, were collected. The occurrence of adverse events including secondary autoimmunity, malignancy and death, and pregnancy outcomes was recorded. Baseline variables including age, disease duration and relapse rate were compared in univariate and logistic regression analyses between groups with different disability outcomes. Results: Over a median 7-year follow-up (range 33–144 months), most patients (52%) required just two cycles of alemtuzumab. In the remaining patients, relapses triggered re-treatment to a total of three cycles (36%), four cycles (8%) or five cycles (1%). Using a 6-month sustained accumulation of disability definition, 59/87 (67.8%) of patients had an improved or unchanged disability compared with baseline. By an area under the curve analysis, 52/87 (59.8%) patients had an overall improvement or stabilisation of disability. Higher baseline relapse rate was associated with worse long-term disability outcomes, with trends for longer disease duration and older age at first treatment. Secondary autoimmunity was the most frequent adverse event occurring in 41/86 (47.7%) patients, most commonly involving the thyroid gland. Conclusions: Alemtuzumab is associated with disease stabilisation in the majority of patients with highly active RRMS over an average seven-year follow-up. No new safety concerns arose over this extended follow-up.